y = 2^x
ln y = ln 2^x
d/dx ln y = d/dx ln 2^x
d/dx ln y = d/dx x*ln 2
Pull the constant (ln 2) out:
y'/y = ln 2 * d/dx x
y'/y = ln 2
y' = y * ln 2
y' = 2^x * ln 2
*** Remember this advice, kids. Whenever you want to get rid of a variable exponent during differentiation, use logarithmic differentiation. Using it will make things cleaner and easier.
2006-11-16 09:34:29
·
answer #1
·
answered by عبد الله (ドラゴン) 5
·
0⤊
1⤋
How can everyone get this wrong?
d/dx (2^x) = d/dx (e^(x ln 2)) = e^(x ln 2) ln 2 = 2^x ln 2
Errors in the other answers:
rubberbandbanker - your method is valid, but in your last step:
"y'/y=ln 2
y'=(xln2)*(ln2)"
y=2^x, not x ln 2 (x ln 2 is ln y, not y)
jj - power rule applies when the base is a variable and the power is a constant, not the other way around
izzyhearts - your formula is transposed. It's a^x ln a, not a ln a^x
2006-11-16 09:37:10
·
answer #2
·
answered by Pascal 7
·
0⤊
0⤋
Surely its x*2^(x-1). It can't be ln2 as ln2=0.693.... which is a constant, and presumably x is a variable?
2006-11-16 09:30:50
·
answer #3
·
answered by jj 2
·
0⤊
0⤋
u take the ln of both sides, then differentiate
lny=xln2
then differentiate
y'/y=ln2
so then u plug in y for y and multiply it so u isolate y'
y'=(x^2)*(ln2)
its right now sorry i made a careless mistake before
2006-11-16 09:28:08
·
answer #4
·
answered by rubberbandbanker 2
·
0⤊
0⤋
y = x^(2x - 3) We are going to find dy using logarithmic differentiation, so first take the natural log of each side: ln(y) = (2x - 3)ln(x) Take the derivative of each side, the left by the log properties for derivatives and the right by the product rule: dy/y = (2x - 3) * 1/x + 2ln(x), which can also be written: dy/y = 2 - 3/x + 2ln(x) Now, multiply both sides by y: dy = y * (2 - 3/x + 2ln(x)) Plug back in, and we're done: dy = (x^(2x - 3)) * (2 - 3/x + 2ln(x))
2016-03-28 22:49:11
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
y=2^x
lny=ln(2^x)
lny=xln2
(dlny/dy)*dy/dx = ln2 dx/dx
(1/y)*dy/dx=ln2
dy/dx=y*ln2
dy/dx=(2^x)*ln2
hope this helps
ur answer is not right
here what u r doing is applying implicit differentiation and the chain rule.
2006-11-16 09:39:57
·
answer #6
·
answered by rendezvous247 1
·
0⤊
0⤋
the answer is 2 ln(2^x). i think.
the formula is a ln(a^x), where a is the coefficient
2006-11-16 09:32:33
·
answer #7
·
answered by izzyhearts 1
·
0⤊
0⤋
y=2^x
log y = log(2^x)
logy = x* log2
Did this helped you
2006-11-16 09:24:19
·
answer #8
·
answered by Kewl guy 3
·
0⤊
1⤋